Analisis Semiotik Puisi “Kematian Dan Makam Mistik” Karya Jalaluddin Rumi (Sekolah Tinggi Agama Buddha Nalanda, 2023)
This research was motivated by the author's admiration for Maulana Jalaluddin Rumi's work and the author's interest in analyzing one of the poems as extraordinary material because there are many meanings and implied signs that need to be studied for meaning. The purpose of this study is to examine meaningfulness based on signs contained in one of Jalaluddin Rumi's poems entitled